Review of influence of steric effect on aggregation behavior of fine particles - Xu, Hongxiang; Tian, Han; Deng, Jiushuai; Zhuo, Qiming; Cui, Jiahua; Wang, Jingzheng; Yin, Yanan; Yu, Peng (Minerals engineering, 2023)
The aggregation and dispersion of fine particles is the macroscopic embodiment of the interaction force between particles. As an important part of the interaction force between particles, the steric hindrance effect has attracted attention of researchers. When long chain surfactant or polymer agent is adsorbed on the mineral surface, a certain adsorption layer will be formed and steric hindrance effect will be produced. The characteristics of the adsorption layer affect the aggregation behavior between particles. In this paper, the discovery, measurement and application of steric hindrance effect in engineering are reviewed, the main affecting steric hindrance factors are discussed, and the quantitative measurement of steric hindrance is prospected. It is expected to provide guidance for the dispersion and condensation of fine particles.